Prognostic Value of Abnormal Liver Function Tests After Mechanical Thrombectomy for Acute Ischemic Stroke - Huang, Kangmo; Zha, Mingming; Xiao, Lulu; Gao, Jie; Du, Juan; Wu, Min; Yang, Qingwen; Liu, Rui; Liu, Xinfeng (Frontiers in Neurology, 2021)
Objective: To determine the clinical significance of post-procedural abnormal liver function test (ALFT) on the functional outcomes at 90 days in acute ischemic stroke (AIS) treated with mechanical thrombectomy (MT). Methods: In this retrospective observational study, patients with AIS undergoing MT were enrolled from the Nanjing Stroke Registry Program and the multicenter Captor trial. A favorable outcome was defined as a modified Rankin Scale score 0–2 at 90 days. Predictive models were established by multivariable logistic regression. Improved predictive value of models was assessed by continuous net reclassification improvement (NRI) and integrated discrimination improvement (IDI). In addition, multivariable logistic regression and restricted cubic spline were used to analyze dose–response correlations between the severity of ALFT and prognosis. Results: Among 420 patients enrolled, 234 (55.7%) patients were diagnosed as post-procedural ALFT after MT. Patients with post-procedural ALFT had higher National Institute of Health Stroke Scale score on admission (median, 18 vs. 15, p < 0.001) and more pneumonia (65.4 vs. 38.2%, p < 0.001) than those without post-procedural ALFT. Post-procedural ALFT, rather than preprocedural ALFT, was independently associated with favorable outcome (adjusted odds ratio, 0.48; 95% CI 0.28–0.81; p = 0.006). The improvement of predictive model after adding post-procedural ALFT was significant [continuous NRI (value, 0.401; p < 0.001), IDI (value, 0.013; p < 0.001)]. However, the restricted cubic spline indicated no evidence of a dose–response relationship between the severity of post-procedural ALFT and prognosis. Conclusions: In AIS patients treated by MT, post-procedural ALFT was associated with more severe stroke and served as an independent predictor of worse prognosis at 90 days.